Z historii stosunków Trzeciej Rzeszy z Irlandią Południową (1939-1945) - Abramczyk, Łukasz (Acta Universitatis Lodziensis. Folia Historica, 2008)
The purpose of (his article is to create the general outlook of diplomatic relationship between Hitler’s Germany and Southern Ireland during Second World War. The article opens with a presentation of limited German and Irish contacts since 1914 to 1921, and general mutual relations before the War. In the next part of the article, both Irish and German conceptions on war policy are being characterised in an attempt to confront harsh Irish policy of neutrality with German endeavours to subodinate De Valera's government. Another problem is related with Abwehra’s trying her hand in cooperation with radical fractions of IRA. Those attempts didn’t result in warming relations between both governments. In another part of this article is desription of German military plans considering invasion of Southern Ireland as a part of operation Seelöwe.